The possibilities to develop the logistics of electrical and electronic waste in the military defence system of the Republic of Serbia - Jovanović, Dragutin V. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The military defence system of the Republic of Serbia (the Ministry of Defence and the Serbian Army) represents a complex organisational and technical-technological system. The nature of its operations imposes it to be equipped with a considerable amount of electrical and electronic equipment and devices. Such equipment and devices during operation, over time, lose their primary function, become useless and turn into electrical and electronic equipment waste; therefore, they must be handled properly. This article discusses the problems and possible directions of the logistics of development and implementation of electrical and electronic waste generated in the defence as the logistics of waste and reverse waste logistics, which is, in a narrower sense, a part of waste materials management. For the purpose of this paper, the logistics of electrical and electronic waste in the defence is regarded as the process of planning, implementation, control and realisation of flows, processes and activities of electrical and electronic waste materials from their place of origin to their place of disposal, through collecting and transportation to the final destination (places of treatment, reuse, disposal and destruction) in order to meet the requirements of all stakeholders at minimal cost. The legislation and European initiatives in the area of electrical and electronic waste In 2003, the European Union, stimulated by the rapid emergence and amount of e-waste, as well as its hazardous influence on the environment, adopted two directives: Directive 2002/96/EC of the European Parliament and the European Council on 27.01.2003 on the management of electrical and electronic waste (WEEE - Waste from Electrical and Electronic Equipment) and Directive 2002/95/EC of the European Parliament and the Council of Europe 27.01.2003 on the restrictions on the use of hazardous substances in electronic and electrical equipment (RoHS - Restriction of the use of hazardous substances). The adopted Directives should improve the management of e-waste and make its treatment safer. Experience of developed countries in dealing with electrical and electronic waste Most of the management of e-waste in the developed countries of Europe and the world is organized around the existing municipal waste collection points. A common thing is the existence of three primary channels for collecting e-waste: municipal collection points, retail stores and direct return to the manufacturer. There is a great diversity in the amount of collected and treated electrical and electronic waste, although different categories of devices and the size of the population were considered. In addition to quantitative measures, various qualitative measures for the management of e-waste are defined: - Environmentally acceptable treatment (Denmark), - Adequate treatment in accordance with the regulations (Norway), - Pre-treatment of waste prior to disposal in landfills (Sweden, Switzerland), - Minimum standards for the treatment, recovery of metals and incineration of chemicals that cannot be restored (Switzerland), - Division of devices into reusable and non-reusable ones (Belgium). Production of electronic and electrical waste in the defence system During the development and technological modernization of the military and defence system as a whole, a substantial part of electrical and electronic equipment and devices is coming into the state when it is either replaced by newer equipment or rejected. Most of such equipment and devices become e-waste. The specificity of e-waste generated in the defence system is its complexity and speed with which electrical products become obsolete and replaced by new ones. Due to rapid technology development, faulty equipment and devices are rarely repaired, but rather replaced with new ones, because it is simpler and often more cost-effective. The average life span of computers has been reduced from six to just two years. The situation is similar with other IT and telecommunications equipment. The amount of e-waste generated in the defence system is growing rapidly, and the content of hazardous substances in electrical and electronic equipment is a major concern of the e-waste management and its recycling that it is not implemented to a sufficient extent. The amount of electrical and electronic waste generated in the defence system In the Republic of Serbia as well as in its defence system there are no exact figures on the amount of e-waste generated in a year. Establishing fully reliable amounts of e-waste is very difficult because there are some difficulties in the quantitative determination of the parameters related to the production and consumption of electrical and electronic devices. Besides that, determining the amount of e-waste in the defence system depends on how much waste is generated in the Army units and in the organizational units of the Ministry (administration and sectors), quantities of old equipment and devices in warehouses, etc. To determine the potential volume of e-waste generated in the defence system, different approaches and methods can be used, depending on the availability of the required data. The European Agency for the Environment has proposed the use of the following methods: - Time-progressive method (Time Step), - Market methods, - Carnegie-Mellon methods, - Approximate methods I and II. The accuracy of the established amount of e-waste depends on the reliability and completeness of the database. To obtain a more reliable estimate of the potential amount of e-waste, it is advisable to simultaneously use a number of possible methods and compare the results. Given the nature of the defence system, to determine the potential volume of e-waste generated in it, it is possible to use the method of gradual time and approximate methods I and II. Activities of electrical and electronic waste logistics To fulfill the requirements of the Directive on e-Waste, it is necessary to establish effective organizational and logistic feedback systems. Collection and transportation must be organized to optimize the reuse and recycling of the components or whole appliances suitable for recycling or reuse. The preservation of devices for reuse requires proper organization and logistic operations of collecting, transporting, sorting, and waste-storage, all in order to preserve the re-usability of the product. Conclusion For successful logistics of e-waste generated in the defence system, it is necessary to continuously work on designing, planning and undertaking certain organizational measures. Designed measures should be taken during the execution of the whole process of e-waste logistics, from collection activities at the source to final disposal activities, either in processing plants or landfills. Some quality performances of e-waste logistics services can be improved. The followingt should be considered: need for development of appropriate systems for the selective collection of e-waste; need for sharing responsibilities within the logistic operations and financial management of e-waste;, possibility of establishing different control mechanisms in the management of waste materials, with efforts to the development of methods for e-waste prevention; development of measures for the prevention of sending e-waste to landfills or incineration lines; difficulties in establishing fully reliable amounts of e-waste due to some uncertainty regarding the production and consumption of electrical and electronic devices; need to establish effective organizational and logistic feedback systems; opportunity and need for the system to define number, capacity, location and organization within a collection point; and training of personnel for proper handling, loading, unloading and reloading of e-waste in order to preserve the ability to re-use it.